Perlindungan Privasi Dan Data Pribadi Konsumen Pada E – Commerce - Wanda Aprilly Charos; Muhammad Irwan Padli Nasution2 (CV. ITTC INDONESIA, 2023)
The online market place system is one form of development of e-commerce activities. Commerce. The online marketplace system provides facilities for online shopping activities which contains various services to make it easier for online consumers (e-consumers). On the other hand, services that make it easier there are potential threats for online consumers, especially related to personal data and online consumer privacy the. This research discusses the protection of personal data and e-consumer privacy on the online marketplace system using normative research methods (legal research). The research approach used is Statute Approach, Conceptual Approach, Case Approach and Comparative Approach. The results of this study appear that the development of e-commerce in Indonesia has been going so fast, at least The state encourages the birth of new start-ups that can take advantage of various programs, one of them is